Fiscal Decentralization and Regional Financial Independence in Indonesia: A Systematic Literature Review - Selly Swandari; Andriawan Kustiawan; Imelda Veronica Gea; Akbar Lufi Zulfikar (PT. Banjarese Pacific Indonesia, 2026)
This study examines the development of fiscal decentralization and its relationship to regional financial independence in Indonesia through a systematic literature review. The objective is to synthesize empirical and conceptual findings published between 2017 and 2026 concerning the determinants, measurement, and consequences of regional financial independence, particularly the role of local own-source revenue (PAD), intergovernmental transfers, and capital expenditure. Using a systematic search of Scopus, Google Scholar, and Garuda databases, 30 relevant articles were screened, selected, and analyzed following defined inclusion and exclusion criteria. The review finds that fiscal decentralization consistently strengthens local revenue mobilization and administrative accountability when accompanied by adequate institutional capacity, transparent governance, and effective management of natural and economic resources. However, the effectiveness of decentralization varies considerably across regions due to disparities in economic potential, human resources, and political commitment. The synthesis further shows that financial independence positively affects the quality of public services and regional economic growth, although the relationship is moderated by expenditure efficiency and governance quality. The novelty of this review lies in its integrative framework linking revenue-side determinants, expenditure behavior, and governance mechanisms within a single analytical narrative, an integration rarely addressed jointly in prior single-country studies. The findings offer practical implications for policymakers designing fiscal transfer formulas and for future researchers seeking to test moderating variables such as digitalization and institutional quality in the fiscal decentralization–financial independence nexus.